Discursive Communication of Covid-19 Vaccination Against Anti-Vaccine Communities (Study at Semanan Subdistrict Government, DKI Jakarta Province) - PRAKOSO, Jatayu Hadi; LESTARI, Puji; JAMALULLAIL, Jamalullail (PT Keberlanjutan Strategis Indonesia, 2023)
Indonesian society faced the Covid-19 pandemic some time ago. On February 13, 2022, the government accelerated vaccination for doses 1 to 2 with 326.62 million vaccine doses. The debate and problem that occurs is that several groups of people reject vaccination, which is called the anti-vaccination community, with responses that give rise to their respective truth claims. The truth claim is expressed in not attending the vaccine center organized by the government. This research aims to see the need for a consensus to reduce the stigma of Covid-19 vaccination in anti-vaccine communities. The gap in this research is the views of the anti-vaccine community regarding the implementation of COVID-19 vaccination in Semanan Village. The discourse approach could be more effective, especially in the anti-vaccination community in the Semanan sub-district area, DKI Jakarta Province. Discursive communication theory is used to identify this communicative action, which suggests the context of Communication, namely ego identity towards truth claim. Findings obtained that, in implementing the COVID-19 vaccination, the community formed an institution with aspects of professionalism, which impacted the implementation of the vaccine center in the Semanan sub-district area. Professionalism institutions consist of opinion leaders, medical roles, and approaches through socio-cultural and socio-religious roles. More than discursive communication competence is required. Humanistic Communication highlights the importance of adding elements of agreeableness, namely how to treat relationships with others to avoid Conflict.